Management of Chronic Pacemaker Lead Infection, Superior Vena Cava Obstruction and Tricuspid Valve Endocarditis (Operative Technique and a Case Report - Husain H. Jabbad (Journal of King Abdulaziz University: Medical Sciences, 2023)
A 73 year old female presented with the diagnosis of infected cardiac pacemaker. She had complete heart block 2.5 years ago, a permanent dual chamber pacemaker was inserted via a left subclavian approach and the pulse generator positioned in the left clavipectoral fascia. In the early post operative period she developed fever with a clear pacemaker pocket infection, treated with intravenous antibiotics. The initial pacemaker was removed, the pocket cleaned and closed and a new dual-chamber pacemaker inserted in the right clavipectoral area via right subclavian approach. She was kept on a prolonged antibiotics course of vancomycin and gentamicin because of sepsis and blood cultures results of Pseudomonas aeruginosa. On presentation she had diabetes insipidus, recurrent low grade fever and impaired renal function, the pacemaker was functioning well and she was still on IV vancomycin. Investigations revealed a large intra-atrial clot attached to the pacemaker lead, the pacemaker and infected intravascular component were removed via median sternotomy and new pacemaker inserted with epicardial atrial and ventricular leads. The intra-operative cultures grow Pseudomonas aeruginosa treated with 6 weeks of intravenous Tazocin, follow-up for 9 months with no recurrent pocket or deep infection and good functioning pacemaker.